2017
DOI: 10.1371/journal.pgen.1006670
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic recombination modulates the structure and dynamics of the synaptonemal complex during C. elegans meiosis

Abstract: During meiotic prophase, a structure called the synaptonemal complex (SC) assembles at the interface between aligned pairs of homologous chromosomes, and crossover recombination events occur between their DNA molecules. Here we investigate the inter-relationships between these two hallmark features of the meiotic program in the nematode C. elegans, revealing dynamic properties of the SC that are modulated by recombination. We demonstrate that the SC incorporates new subunits and switches from a more highly dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
143
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 56 publications
21
143
0
Order By: Relevance
“…Consistent with our model, the central region of the SC remains dynamic in later stages of meiosis in syp-4 phosphodead mutants (this study) and in meiotic recombination defective mutants (Machovina et al, 2016; Pattabiraman et al, 2017). Moreover, the observation that the SC persists in a more dynamic state during pachytene in spo-11 mutant animals (Machovina et al, 2016; Pattabiraman et al, 2017), despite the lack of programmed meiotic DSB formation in this mutant, rules out the possibility that the elevated DSB levels observed in syp-4 phosphodead mutants cause the prolonged dynamic state of the SC.
10.7554/eLife.23437.024Figure 7.Model for how PLK-1/2-dependent phosphorylation of the synaptonemal complex protein SYP-4 regulates double-strand break formation through a negative feedback loop.In wild type, PLK-1/2-dependent phosphorylation of SYP-4 at the S269 site occurs in response to CO designation. This phosphorylation switches the central region of the SC from a more dynamic (pink) to a less dynamic state (blue) during pachytene, inhibiting additional DSB formation on the homologous chromosomes.
…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our model, the central region of the SC remains dynamic in later stages of meiosis in syp-4 phosphodead mutants (this study) and in meiotic recombination defective mutants (Machovina et al, 2016; Pattabiraman et al, 2017). Moreover, the observation that the SC persists in a more dynamic state during pachytene in spo-11 mutant animals (Machovina et al, 2016; Pattabiraman et al, 2017), despite the lack of programmed meiotic DSB formation in this mutant, rules out the possibility that the elevated DSB levels observed in syp-4 phosphodead mutants cause the prolonged dynamic state of the SC.
10.7554/eLife.23437.024Figure 7.Model for how PLK-1/2-dependent phosphorylation of the synaptonemal complex protein SYP-4 regulates double-strand break formation through a negative feedback loop.In wild type, PLK-1/2-dependent phosphorylation of SYP-4 at the S269 site occurs in response to CO designation. This phosphorylation switches the central region of the SC from a more dynamic (pink) to a less dynamic state (blue) during pachytene, inhibiting additional DSB formation on the homologous chromosomes.
…”
Section: Discussionsupporting
confidence: 90%
“…At meiosis onset, the PLK-2 polo-like kinase is enriched at the nuclear envelope attachment sites of chromosome ends, where it promotes homologous pairing and synapsis [ 60 , 61 ]. In late pachytene, PLK-2 re-locates to discrete domains along the SC, marking local enrichment of recombination factors [ 62 , 63 ]. PLK-2 redistribution also occurs before SYP-1 redistribution to the short arm of the bivalent and influences the SC structure [ 62 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the course of analyzing SC assembly over a time course of meiotic progression in our mutants we obtained an unexpected finding: SCs assembled in zip3, zip1[D2-9] and zip1 [10][11][12][13][14] strains (corresponding to SCs assembled in the absence of MutSg crossovers) assemble earlier than wild-type SC structures, and appear to be less capable of persisting during an ndt80mediated, meiotic prophase arrest ( Figure 3). Pattabiraman (2017) found that a MutSg-associated process affects the dynamic properties of C. elegans SC [33]; our set of preliminary observations raises the intriguing possibility that the MutSg crossover pathway influences the structure and/or dynamics of budding yeast SCs in a similar fashion.…”
Section: Scs Assembled In the Absence Of Mutsg Crossing Over In Buddimentioning
confidence: 54%
“…Taken together, these data suggest that intermediate events in the budding yeast meiotic recombination process mediate the gradual, stepwise assembly of a recombination intermediate-associated complex that has the capacity to trigger SC elaboration. Interestingly, even in C. elegans where SCs assemble in the absence of recombination initiation, MutSg-associated crossover recombination intermediates locally influence the physical and dynamic properties of the C. elegans SC, through a Polo-like kinase (PLK-2) signaling mechanism [33]. The observed interdependencies between synapsis and meiotic recombination indicate that the two processes are not only spatially correlated but that the mechanisms involved in each process are functionally intertwined, however we currently lack a substantial molecular understanding of the how these hallmark meiotic processes intersect.…”
Section: Introductionmentioning
confidence: 99%